GLOBALIZING JAVANESE CULTURE THROUGH LITERARY TRANSLATION: A CRITICAL DISCOURSE ANALYSIS OF JAVANESE TERMS IN RATIH KUMALA’S GADIS KRETEK - Eka Yunita Liambo; Ika Oktaviana; Rosdiana Puspita Sari (Universitas Islam Sumatera Utara (UISU), 2026)
This study analyzes Javanese cultural terms in Ratih Kumala’s Gadis Kretek and their English translations within the context of cultural globalization. As a contemporary Indonesian novel rich in local cultural expressions, Gadis Kretek presents challenges for translators in mediating Javanese social practices and cultural values for international readers. This study aims to identify Javanese cultural terms, classify them according to Katan’s cultural levels (surface, formal, and deep culture), and examine their ideological implications using Fairclough’s Critical Discourse Analysis framework. The data are drawn from the Indonesian source text and its official English translation, translated by Annie Tucker and published by Monsoon Books in 2016 (2024 edition). Employing a qualitative discourse analysis approach, this study compiled 167 culture-specific items and analyzed their corresponding renderings in the target text. Translation strategies were identified based on Baker’s taxonomy and interpreted through Venuti’s domestication and foreignization frameworks. The findings reveal a predominance of domestication-oriented strategies, particularly cultural substitution and neutralization, alongside selective foreignization through loan-word retention. This pattern indicates an ideological tendency to prioritize accessibility for global audiences while partially maintaining Javanese cultural markers. As a result, the cultural meanings intended for global introduction are not fully transmitted, as domestication tends to simplify, generalize, or dilute culture-specific nuances embedded in the source text. In this respect, the study demonstrates that translation acts as a mediating practice that reshapes cultural identity in globalization by negotiating between cultural visibility and readability, contributing to discourse-oriented research in literary translation.